The role of demographic diversification of the police force in curbing hate crimes: cross-sectional and longitudinal analyses. (4th May 2022) - Sweeney, Matthew M.; Chenane, Joselyne L.; Perliger, Arie
ABSTRACT: A growing body of evidence shows that minorities are disproportionately targeted for hate crimes. However, few studies have examined how increasing the representation of minority officers in police departments can impact hate crime rates. Drawing on cross-section and longitudinal data from sources such as Law Enforcement Management and Administration Statistics (LEMAS), the U.S. Census, and Challengers from the Sidelines, the current study examines the relationship between police diversity and hate crimes. We hypothesize that high levels of police diversity will be associated with low hate crime rates. Moreover, we argue that the relationship between police diversity and hate crimes is moderated by police departments' geographic location (urban, rural, and suburban), hate crime laws, and high-profile hate crime cases. The findings reveal that police diversity is associated with low hate crime rates in our longitudinal analyses. Also, the police diversity-hate crime nexus is moderated by geographic location, suggesting the effect of police diversity on hate crimes was stronger in urban police districts relative to suburban and rural districts. Our findings move beyond prior studies by proposing conditions under which police diversity may be most meaningful. Thus, police diversity can help reduce hate crimes, particularly in urban districts.